A study on factors that influencing internet addiction among public university students in Malaysia / Jenny Lusat and Martina Francis Banyi - Lusat, Jenny; Francis Banyi, Martina (2022)
The aim of the study is to identify the factors that influence internet addiction among public university students in Malaysia by examining the relationship between personal and psychological factor, family related factor, and perceived internet characteristic with internet addiction. To test the hypothesis of the study, a quantitative method and cluster sampling was used by distributing online questionnaires to public university students in Malaysia and a total of 370 responses were received. The results suggested that there is a significant positive relationship between the personal and psychological factor, family related factor, and perceived internet characteristics with internet addiction. Hence, it shows that the three independent variables identified in the study are influencing internet addiction among public university students in Malaysia. This study gives a better understanding of internet addiction and what factors that may lead to internet addiction among university students.